Evaluación del rendimiento de tres variedades de pepinillo (Cucumis sativus L.) con sustrato hidropónico en La Esperanza - Trujillo - Vasquez Gastañadui, Iris Noemi (2017)
The present research aimed to determine the yield of three varieties of gherkin (Cucumis sativus L.) with hydroponic substrates. Each experimental unit was formed by a geomembrane sleeve, direct seeding was carried out and the experiment was conducted in a greenhouse. The treatments under study were T1 (100% quarry sand with Marketmore variety), T2 (100% quarry sand with Palomar variety), T3 (100% quarry sand with Hybrid Thunderbird), T4 (50% quarry sand plus 50% moss with the variety Marketmore), T5 (50% quarry sand plus 50% moss with Palomar variety), T6 (50% quarry sand plus 50% moss with Hybrid Thunderbird). The treatments were distributed using the statistical design of Complete Blocks Random (DBCA), with factorial arrangement (2x3) two substrates and three varieties, with six treatments and three replicates. To determine the best treatment, an analysis of variance and the Duncan test of means at the 5% level of significance. The highest yields were the treatments T6 and T3 were statistically similar obtaining (27.79 and 25.75 kg/m2), the highest average weight per fruit with (543.98 and 543.04 g), the highest number of fruits per plant with (26 and 24 fruits), However the T6 treatment also stood out in the longest fruit length and fruit diameter with (29.11cm) (6.00cm) respectively.